2018
DOI: 10.1016/j.anorl.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Management of otitis media with effusion in children. Société française d’ORL et de chirurgie cervico-faciale clinical practice guidelines

Abstract: The Société française d'ORL et de chirurgie cervico-faciale clinical practice guidelines concern the management of otitis media with effusion (OME) in children under the age of 12 years. They are based on extensive review of MEDLINE and Cochrane Library publications in English or French from 1996 to 2016 concerning the methods of diagnosis and assessment of otitis media with effusion, as well as the efficacy of tympanostomy tubes and medical and surgical treatments of OME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
0
11
0
12
Order By: Relevance
“…Another literature review of 10 randomized studies found that the hearing threshold had improved after TT placement, with a gain [95%CI] of 12 dB (Fergie et al., 2004; Rayner et al., 1998; Hall-Stoodley et al., 2006; Van Hoecke et al., 2016; Potera, 1999) in the first three months and 4 dB (Blanc et al., 2018; Casselbrant and Mandel, 2003; Flynn et al., 2009; Maris et al., 2014; Maw et al., 1999) from 6 to 9 months. However, the review did not find any evidence of a long-term effect of TTs on comprehensive and expressive language development (Browning et al., 2010).…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another literature review of 10 randomized studies found that the hearing threshold had improved after TT placement, with a gain [95%CI] of 12 dB (Fergie et al., 2004; Rayner et al., 1998; Hall-Stoodley et al., 2006; Van Hoecke et al., 2016; Potera, 1999) in the first three months and 4 dB (Blanc et al., 2018; Casselbrant and Mandel, 2003; Flynn et al., 2009; Maris et al., 2014; Maw et al., 1999) from 6 to 9 months. However, the review did not find any evidence of a long-term effect of TTs on comprehensive and expressive language development (Browning et al., 2010).…”
Section: Treatmentsmentioning
confidence: 99%
“…The North American (Rosenfeld et al., 2013), (Rosenfeld et al., 2016), (Rosenfeld et al., 2004) and French (Blanc et al., 2018) guidelines recommend a 3-monthwait-and-see period prior to TT placement.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de ello en un estudio de Hellström no se encuentran evidencias de una mejoría en la calidad de vida ni en la audición más allá de 9 meses tras la colocación de tubos de equipresión [12]. Otros estudios muestran que la mejoría en los umbrales auditivos tras colocar tubos de ventilación en de alrededor de 12 dB HL en los primeros tres meses [13][14][15] y no más de 5 dB de 6 a 9 meses tras su colocación [16,17] no habiéndose descrito evidencia alguna de su beneficio en cuanto a la inteligibilidad del lenguaje hablado o de un mayor desarrollo verbal en los niños que les portan [18]. En cualquier caso, los tubos transtimpánicos constituyen una primera línea de tratamiento bajando su eficacia sea el parámetro que se estudie entre los 6 y 18 meses tras su colocación [9] siendo universalmente recomendados en niños con disfunción crónica de su trompa de Eustaquio.…”
Section: Discussionunclassified
“…6-8 These recommendations have been adopted, in part, by other countries publishing guidelines on OME that secondarily discuss tympanostomy tubes. 9-13 As such, the AAO-HNSF guideline remains the only publication explicitly focused on tympanostomy tube indications and managing children who receive tubes.…”
Section: Update Rationale and Scopementioning
confidence: 99%